An Efficient Solid-Phase Green Synthesis of Chromen-2-one Derivatives - Tasqeeruddin, S.; S. Al-Arifi, Abdullah; Dubey, P.K. (Asian Journal of Chemistry, 2013)
An efficient route for the synthesis of chromen-2-one derivatives (3a-h) via Knoevenagel condensation under solid phase by the condensation of salicylaldehydes (1) with various ethyl acetate derivatives (2) is described. The reaction has been done under conventional method as well as under solid-phase method. The later method has been found to be much better in terms of time and yield. The structures of all the compounds were confirmed by spectral and analytical data.